1985
DOI: 10.1007/bf02099751
|View full text |Cite
|
Sign up to set email alerts
|

Tubulin evolution: Ciliate-specific epitopes are conserved in the ciliary tubulin of metazoa

Abstract: In spite of their overall evolutionary conservation, the tubulins of ciliates display electrophoretic and structural particularities. We show here that antibodies raised against Paramecium and Tetrahymena ciliary tubulins fail to recognize the cytoplasmic tubulins of all the metazoans tested. Immunoblotting of peptide maps of ciliate tubulins reveals that these antibodies react with one or very few ciliate-specific epitopes, in contrast to polyclonal antibodies against vertebrate tubulins, which are equivalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…By immunoblot analysis, we demonstrated that antibodies directed against PA tubulin (18,19) did not react with higher plant tubulin (Fig. 1A).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…By immunoblot analysis, we demonstrated that antibodies directed against PA tubulin (18,19) did not react with higher plant tubulin (Fig. 1A).…”
Section: Resultsmentioning
confidence: 96%
“…Tubulin concentrations were determined according to Bradford (22), and purity was assessed by SDS/PAGE (23). Anti-PA-tubulin-specific antibodies (18,19) were affinity-purified (15).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Paramecium axonemal tubulin and the specific, affinity-purified antibody against this tuhniin were prepared as previously described (Adoutte et at., 1985;Cohen et at., 1982;Geuens et at., 1989).…”
Section: Tubulin and Antitubulin Preparationmentioning
confidence: 99%
“…We have used, however, a newly developed tool consisting of unmodified Paramecium ciliary tubulin and a polyclonal antibody (Cohen et al, 1982) which reacts strongly with this tubulin but is totally unreactive with vertebrate cytoplasmic or mitotic tubulins (Adoutte et al, 1985). It appeared, therefore, that we might be able to follow specifically the in vivo incorporation of Paramecium tubulin into the MTs of a vertebrate cell by using this specific antibody.…”
mentioning
confidence: 99%